Effectiveness of protective clothing for motorized 2-wheeler riders. (17th February 2019) - Wu, Dan; Hours, Martine; Ndiaye, Amina; Coquillat, Amandine; Martin, Jean-Louis
Abstract: Objective: This study assesses the effectiveness of protective clothing (motorcycle jacket, trousers, gloves, knee-high or ankle boots, back protection) for motorized 2-wheeler (MTW) riders. Methods: This retrospective observational study used injury data from the Rhône Registry of Road Accident Victims, plus a postal survey conducted in 2016. Seven thousand one hundred forty-eight MTW riders involved in accidents between 2010 and 2014 were identified from the Registry and were invited to complete a questionnaire. Nine hundred seventy-nine individuals returned the questionnaire with relevant information; 951 with complete injury descriptions and clothing information were included in the study. The impact of protective clothing on injury risk was estimated using Poisson regression, with weighting for nonrespondents. Results: Sixty-seven percent of MTW riders sustained upper limb injuries and 47% sustained lower limb injuries. Gloves were the most frequent gear worn (76%), followed by jackets (59%) and knee-high or ankle boots (37%). Only 23% had back protection and 0.3% had an airbag. Wearing protective clothing was associated with a lower risk of soft tissue injury to upper and lower limbs: For upper limbs, the risk was lower when one of 2 items (a motorcycle jacket or gloves) was worn (relative risk [RR] = 0.36; 95% confidence interval [CI], 0.18–0.75) and was lowest when both were worn (RR = 0.28; 95% CI, 0.12–0.69); for lower limbs, risk was reduced by wearing both motorcycle trousers and boots (RR = 0.60; 95% CI, 0.40–0.91) but was not significantly reduced when only one of these items was worn (RR = 0.90; 95% CI, 0.67–1.21). This protective effect was mainly due to a reduction in abrasions/lacerations rather than contusions. However, protective clothing did not reduce the risk of fracture, dislocation, or sprain, except for knee-high or ankle boots, which were associated with lower risk of ankle or foot fracture (RR = 0.43; 95% CI, 0.24–0.75). No effect of back protectors was shown. Conclusions: This study confirms the potential for motorcycle clothing to protect users from injury, in particular abrasions and lacerations. However, it did not show any significant protective effect against more serious injuries, such as fracture, dislocation, or sprain, except for knee-high or ankle boots, which reduced foot and ankle fracture risk. Our results argue for more widespread use of protective clothing by MTW users.